Water polo shot indicators according to the phase of the championship: medallist versus non-medallist players - Garcia-Marin, P.; Argudo Iturriaga, F. M. (International Journal of Performance Analysis in Sport, 2017)
The objective of this study was to compare the technical and tactical water polo shot indicators between medallist and non-medallist teams in the preliminary and final phases of the XV FINA Women`s World Championship and to compare shot indicators between both phases of the championship for each classification category. A nomothetic observational, multidimensional and longitudinal design was used. A total of 2463 throws recorded in 44 matches were studied using match analysis. A descriptive and covariance analysis was performed with the univariate general linear model. The difference in the number of goals in the final score was introduced as a covariate. In both phases of the championship, significant differences (p = .05) were found between medallist and non-medallist players in equality and counterattack. Significant differences were also found in power play, but only in the preliminary phase. Penalty shot indicators were similar for all teams in both phases of the championship. The dynamics of the medallist players` throws varied in more indicators and situational frameworks from the preliminary phase to the final phase when compared with the non-medallist players. Match analysis allowed the discrimination of performance factors in medallist and non-medallist players and suggested practical applications for throw training.